Estudo de caso: proposta de implantação de conceitos da indústria 4.0 para a coleta e controle de indicadores operacionais em uma estação de tratamento de água e efluentes - Massei, Alexandre Nocera (Universidade Federal de São Carlos, 2022)
Currently, in Brazilian industries, it is common to find routine procedures and data control performed on paper, or in an offline mode. With the context of COVID-19, the number of employees working face-to-face in factories has decreased, both because of the pandemic and the hybrid working model. With this, access to information in these routines, such as the collection of operational indicators, and the execution of these routines has been hampered. To solve this problem many companies are adopting strategies based on Industry 4.0 concepts and applications with the aim of transforming their procedures digital and decentralized, with as little human effort as possible. Industry 4.0 can be explained as a revolution in factory connectivity, associating people, machines, information, and knowledge. A more connected factory is able to make decisions faster, and in a more assertive way, since it will be based on more reliable data, processed in real time, with only computational effort. With greater efficiency and quality in operational work, strategic work can come more into focus. In this paper a case study was explored, on how Ingredion's water and wastewater treatment plant in Mogi Guaçu - SP was able to use common Industry 4.0 concepts to transform a routine procedure, the collection of operational indicators, which was done in a totally manual and paper-based way, to an automatic, digital and decentralized process. This approach brings new insights for the expansion of Industry 4.0 in Brazil, both with the human view of the changes that took place, and the technical view of how these changes impact the process as a whole. In this way, the objective of the work was to present inputs and results of a real example of the application of Industry 4.0 to solve a common problem, the collection of daily operational indicators of production, as well as the solution for the digitalization of these data and future display of them in a decentralized and agile way, built from the author's internship. In the work, which followed the methodology of presenting the main concepts used for subsequent practical application with the case study, it can be evidenced the improvements presented after the implementation of the project, such as savings in time for data collection and compilation, bringing an improvement of at least 2 hours a week in these aspects, and opening space for various analyses that were not done.
Case study: proposal to implement industry 4.0 concepts for the collection and control of operational indicators in a water and effluent treatment plant
Keywords: Indústria 4.0; Coleta e controle de indicadores operacionais; Estação de tratamento de água; Estação de tratamento de efluentes; Industry 4.0; Collection and control of operational indicators; Water treatment plant; Effluent treatment plant; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA